Pengembangan Lembar Kerja Peserta Didik (LKPD) Interaktif pada Mata Pelajaran PAI dan Budi Pekerti di SMKN 2 Teluk Kuantan - Roni Putra (Departement of Mathematics Education, 2023)
This research aimed at making interactive student worksheets design, and to know the validity and practicality of student worksheets development on Islamic education and moral subject at State Vocational High School 2 Teluk Kuantan. It was a research and development (R&D). This research used 4D models (define, design, development, and dissemination).The product produced in this research was interactive student worksheets on Islamic education and moral subject using Flip Pdf Corporate App. Product validation was conducted by 10 validators consisting of stakeholders and IT experts that were tested to 32 students of XII TKJ grade at State Vocational High School 2 Teluk Kuantan. The questionnaire was used for collecting the data. The data were analyzed to know validity and practicality. Categorization of validity results used the technique proposed by Riduwan: 0-20 Invalid, 21-40 Less valid, 41- 60 Fairly valid, 61-80 Valid, 81-100 Very valid. The results of general validation by 10 validators showed that interactive student worksheets were 84.63% in very valid category. The validation results of the contents feasibility aspect were 84.66%, the presentations feasibility aspects were 84.57%, and the language assessments aspect were 84.66% in very valid category. While, in general, the tried out by 32 students showed that interactive student worksheets were 85.91% very practical to use in the learning process. The results of practicality in the display aspect were 86.87%, in the materials presentation aspect were 85.31%, and in the benefits aspect were 85.20% in very practical category. The validation results by 10 validators and tried out to 32 students showed that interactive student worksheets were very effective to be used in the learning process.